Test Bank for Stewart's Calculus - Tomhave, William (Thomson Brooks/Cole, 2005)
Stewart's MULTIVARIABLE CALCULUS: CONCEPTS AND CONTEXTS, Third Edition offers a streamlined approach to teaching calculus, focusing on major concepts and supporting those with precise definitions, patient explanations, and carefully graded problems. MULTIVARIABLE CALCULUS: CONCEPTS AND CONTEXTS is highly regarded because it has successfully brought peace to departments that were split between reform and traditional approaches to teaching calculus. Not only does the text help reconcile the two schools of thought by skillfully merging the best of traditional calculus with the best of the reform movement, it does so with innovation and meticulous accuracy